The Social Media Paradox: A Correlation Analysis of Fear of Missing Out and Social Anxiety in Adolescent Social Media Users - Ristianingsih; Siti Fitriana; Venty (Bisma The Journal of Counseling, 2025)
The development of social media has expanded the social interaction of adolescents, but also triggered the emergence of Fear of Missing out (FoMO) the fear of being left behind from the experiences of others or those around them. This phenomenon is thought to contribute to increased social anxiety. The purpose of this study was to analyze the empirical relationship between FoMO and social anxiety in adolescent social media users. The subjects of this study consisted of 84 students of Class XI were selected through saturated sampling technique. Data collection was conducted using the FOMO scale based on the theory of Pryblylski and the scale of social anxiety which has been tested for validity (r ≥ 0.30) and reliability (α >0.89). Data analysis using pearson product Moment correlation. The results showed no significant relationship (r = 0.012; p = 0.911) between FoMO and social anxiety. These findings indicate that FoMO does not directly affect social anxiety, but rather is moderated by internal factors such as self-regulation and social support. The implications of this research are important for guidance and counseling practices in developing interventions that focus on strengthening emotion regulation, not just reducing social media use.